Gradual reduction of free sugars in beverages on sale by implementing the beverage checklist as a public health strategy. (15th March 2018) - Luger, Maria; Winzer, Eva; Schätzer, Manuel; Dämon, Sabine; Moser, Nadine; Blagusz, Karin; Rittmannsberger, Barbara; Schätzer, Julia; Lechleitner, Monika; Rieder, Anita; Hoppichler, Friedrich
Abstract: Background: Sugar-sweetened beverages (SSBs) are a major source of free sugar intake and contribute to obesity and obesity-related diseases. Therefore, we analyzed the effect of a gradual sugar reduction strategy within the so-called 'beverage checklist' on free sugar content in beverages on sale in Austria. Methods: From 2010 until 2017, data on the amount of free sugar of sweetened beverages (sweetened with sugars, fruit juice and artificial sweeteners) with 0.20–0.75l serving sizes in all main supermarkets and from industry was collected. These data were published annually as the beverage checklist, which displays beverages on sale in Austria. The checklist aims to encourage beverage production with a free sugar content of ≤7.4 g/100 ml and no artificial sweeteners. Results: Free sugar content in the total supply decreased significantly [7.53 (2.86) vs. 6.75 (2.79) g/100 ml; 10.4%; P < 0.001] over time and also in those for which follow-up data were available until 2017 ( n = 100) [7.55 (2.46) vs. 7.28 (2.44) g/100 ml; 3.5%; P < 0.001]. The percentage of beverages fulfilling the guiding criteria increased by 12.8% ( P < 0.001) and of those containing sweeteners decreased by 13.3% (after 2012; P = 0.034). Conclusions: This public health strategy, conducted by a small non-profit organization, showed a reduction in the mean free sugar content by working with the industry to voluntarily reformulate beverages. More beverages with less added sugar were brought to the market, which implies healthier choices. The challenge now is to further engage the industry and also policy makers to achieve a greater reduction in the future.